Antibody-drug conjugates as game changers in bladder cancer: current progress and future directions - Zhang, Fei; Li, Sheng (Frontiers in Immunology, 2025)
IntroductionAntibody-drug conjugates (ADCs) have emerged as a transformative therapeutic modality in oncology, offering unprecedented precision in targeting tumor cells while sparing healthy tissues. In bladder cancer, a malignancy with high recurrence rates and limited treatment options, ADCs have demonstrated remarkable efficacy by targeting specific tumor-associated antigens such as NECTIN-4 and Human Epidermal Growth Factor Receptor 2 (HER2). This review provides a comprehensive evaluation of the current landscape of ADC-based therapies for bladder cancer, focusing on their mechanisms of action, clinical efficacy, and safety profiles.MethodsWe systematically analyze 232 clinical trials from 2004 to 2025, revealing a significant upward trend in ADC research, particularly following the Food and Drug Administration’s (FDA) accelerated approval of Enfortumab vedotin in 2019. ResultsOur findings highlight the predominance of HER2, NECTIN4, and PD-1 as the most extensively studied molecular targets, with a growing interest in combining ADCs with immune checkpoint inhibitors. Geographically, the United States and China lead in ADC clinical trials, reflecting robust research investment and infrastructure. Discussionespite the promising advancements, challenges such as toxicity management, patient stratification, and trial design remain critical. This review underscores the importance of continued innovation in ADC technology and personalized approaches to overcome these limitations, ultimately paving the way for more effective and safer treatment options for bladder cancer patients. The future of ADC therapy in bladder cancer is bright, with immense potential to revolutionize the standard of care and improve patient outcomes globally.